2017
DOI: 10.1002/jsfa.8308
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of lipidic extracts of saladette tomato pomace and Serenoa repens on prostate and bladder health in obese male Wistar rats

Abstract: These findings indicated impaired contractility and hyperplasia in the prostate and bladder of obese rats induced by high sucrose. STP and SR could enhance prostate function by reducing contractility and hyperplasia and improve smooth muscle fiber structure and decrease cell proliferation in the bladder, suggesting their possible health-beneficial effects on lower urinary tract symptoms. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Exogenous administration of testosterone in experimental animal models had a significant increase of weight prostate 14–16 . These data directly demonstrate that exogenous androgen stimulation significantly increases the weight of the prostate gland, and in severe cases, completely obstructs the urethra generating LUTS 28,29 . Urinary retention due to BPH originates inflammation and urinary tract infections due to prolonged storage of urine.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Exogenous administration of testosterone in experimental animal models had a significant increase of weight prostate 14–16 . These data directly demonstrate that exogenous androgen stimulation significantly increases the weight of the prostate gland, and in severe cases, completely obstructs the urethra generating LUTS 28,29 . Urinary retention due to BPH originates inflammation and urinary tract infections due to prolonged storage of urine.…”
Section: Discussionmentioning
confidence: 64%
“…As an adaptive response to increased urine volume, the bladder undergoes morphological changes generating bladder hyperactivity. 9,28,29 bladder weight, decreased diuresis and increased inflammatory markers, while the treatments improved urinary retention due to decreased prostate volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 162 ] 5. [ 50 ] Silybum marianum Asteraceae Silymarin Seed Reduced contractile response in cystitis CYP-induced cystitis rat model Antioxidant and anti-inflammatory effects [ 40 ] Solanum lycopersicum Solanaceae Saladette tomato Fruit (lipidic extract) Decreased contractility and hyperplasia, improved smooth muscle fiber structure and reduced cell proliferation in the bladder High-carbohydrate diet induced obese Wistar rats (male) NA [ 41 ] Solidaginis virgaurea Asteraceae European golden rod Whole plant Inhibit Carbachol and KCl-induced contractions Rat and human bladder strips Direct antagonistic effect on muscarinic receptors [ 21 ] Uncariae Ramulus Cum Uncis Rubiaceae Gambir Plant, gōu ténɡ 钩藤 Branch with hooks (Rhynchophylline) 1. Inhibited the contraction of urinary bladder strips 2.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used to treat diarrhoea and stomach ache, and served as a diuretic and sexual tonic [ 154 ]. Several clinical studies showed that administration of saw palmetto ( Serenoa repens ) extract improved the IPSS in patients with LUTS and alleviated urodynamic symptoms including urination frequency and nocturia [ 41 , 51 , 74 ]. In a clinical research encompassed 591 patients with inflammation assosciated chronic benign prostate conditions, saw palmetto extract (SPE) mitigated bladder voiding, LUTS as well as erectile function, and improved IPSS and National Institute of Health—Chronic Prostatitis Symptom Index (NIH-CPSI) [ 51 ].…”
Section: Introductionmentioning
confidence: 99%